The Influence of Financial Literacy, Financial Inclusion and Self-Control on Student Financial Management - Septriana, Laras; Ulin Nuha, Muhammad; Yusroni, Nanang (Universitas Wahid Hasyim Semarang, 2025)
Personal financial management must be carried out by every individual, including students. Students with increasing needs, lifestyles, and consumer attitudes need to make them smart in managing their finances. The purpose of this study was to determine whether financial literacy, financial inclusion and self-control have an effect on students' financial management. The sample collection method in this study used incidental sampling with a total of 70 respondents. The independent variables of this study are financial literacy, financial inclusion and self-control. The dependent variable of this study is student financial management. The type of data collected is primary data by distributing questionnaires then processed using SPSS 22. The results of this study partially show that Financial Literacy, Financial Inclusion and Self-Control have a positive and significant effect on Student Financial Management.